Value Relevance of Accounting Information in the United Arab Emirates - Barzegari Khanagha, Jamal (International Journal of Economics and Financial Issues, 2011)
This paper examines the value relevance of accounting information in per and post-periods of International Financial Reporting Standards implementation using the regression and portfolio approaches for sample of the UAE companies. The results obtained from a combination of regression and portfolio approaches, show accounting information is value relevant in UAE stock market. A comparison of the results for the periods before and after adoption, based on both regression and portfolio approaches, shows a decline in value relevance of accounting information after the reform in accounting standards. It could be interpreted to mean that following to IFRS in UAE didn’t improve value relevancy of accounting information. However, results based on and portfolio approach shows that cash flows’ incremental information content increased for the post-IFRS period. Keywords: Value Relevance, IFRS, Accounting Information, UAE